Mobilization, Isolation and Characterization of Stem Cells from Peripheral Blood: a Systematic Review - Natali Yosupov; Haim Haimov; Gintaras Juodzbalys (Stilus Optimus, 2017)
Objectives: The purpose of this article is to systematically review the methods of mobilization, isolation and characterization of stem cells from peripheral blood and to discuss their potential therapeutic applications for bone tissue regeneration. Material and Methods: An electronic literature search was performed through MEDLINE (PubMed) electronic database. The search was restricted to English language articles published during the last 10 years, from January 2006 to November 2016. Results: In total, 37 literature sources were reviewed, and 11 of the most relevant articles that are suitable to the criteria were selected. Articles were analysed with data on animals and humans for mobilization, isolation and characterization of stem cells from peripheral blood. From the examination of selected articles, the mobilization materials, side effects, alternatives and factors affecting the extracted amount of mesenchymal stem cells (MSC) from mobilized peripheral blood of healthy individuals, as well as characterization of mobilized MSC were reviewed in this article. Conclusions: Bone tissue engineering is a potential alternative strategy in bone regeneration and bone defect repair, however, insufficiency data display in the literature on potential therapeutic applications of peripheral blood stem cells for bone tissue regeneration.